Biotreatment efficiency, hydrolytic potential and bacterial community dynamics in an immobilized cell bioreactor treating caper processing wastewater under highly saline conditions. (April 2021) - Zerva, Ioanna; Remmas, Nikolaos; Melidis, Paraschos; Ntougias, Spyridon
Highlights: Caper processing wastewater was effectively treated at 100 g/L salinity. Inhibition of non-halotolerant microbiota above 20 g/L salinity. Hydrolytic potential was negatively affected above 20 g/L salinity. Richness and evenness were reduced during transition to hypersaline conditions. A distinct network of halotolerant bacteria was formed at hypersaline conditions. Abstract: Although caper processing wastewaters (CPW) are characterized by high organic content and salt concentration, no attempt has been made to treat these effluents. In this study, an immobilized cell bioreactor efficiently treated CPW even at hypersaline conditions (100 g/L salinity). Nitrogen was mainly assimilated during biotreatment, as nitrification was inhibited at elevated salinities. The hydrolytic potential was assessed by determining glucanase, xylanase, glucosidase, lipase and protease activities, which were negatively affected above 20 g/L salinity as the consequence of the inhibition of non-halotolerant microbiota. Succession of non-halotolerant taxa by the slightly halotolerant bacteria Defluviimonas, Amaricoccus, Arenibacter, Formosa and Muricauda, and then by the moderately/extremely halotolerant genera Halomonas, Roseovarius and Idiomarina occurred over salinity increase. Diversity indices were reduced during transition from moderately saline to hypersaline conditions. A distinct network was formed at hypersaline conditions, consisting of the halotolerant genera Halomonas, Idiomarina, Saliterribacillus and Gracilibacillus .